Back to the Future: Celebrating Thirty Years of Diversity - Deaville, James (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2000)
A survey of the history of the CAUSM Journal/Canadian University Music Review from its founding in 1971 reveals how the journal, its contents, and policies have reflected conditions within Canada in general and Canadian musical academe in particular, whereby it has been a scholarly publication that above all has been marked by diversity and border crossing throughout its history.